2012
DOI: 10.1111/j.1540-5885.2012.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

The Innovation Value Chain in New Technology‐Based Firms: Evidence from theU.K.

Abstract: Innovation is central to the survival and growth of firms, and ultimately to the health of the economies of which they are part. A clear understanding both of the processes by which firms perform innovation and the benefits which flow from innovation in terms of productivity and growth is therefore essential. This paper demonstrates the use of a conceptual framework and modeling tool, the innovation value chain (IVC), and shows how the IVC approach helps to highlight strengths and weaknesses in the innovation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 113 publications
7
73
1
4
Order By: Relevance
“…Product managers could accumulate numerous opinions and information related to technology, and they used high levels of R&D outsourcing because the technology was stable. This result is consistent with NPD literature, which indicated that external R&D resources complement internal R&D knowledge sources (Ganotakis & Love, 2012). In addition, the contract manufacturers designed new products for other competitors, and the brand owner attempted to obtain market knowledge of other competitors through the contract manufacturers.…”
Section: Auxiliary Productssupporting
confidence: 89%
See 4 more Smart Citations
“…Product managers could accumulate numerous opinions and information related to technology, and they used high levels of R&D outsourcing because the technology was stable. This result is consistent with NPD literature, which indicated that external R&D resources complement internal R&D knowledge sources (Ganotakis & Love, 2012). In addition, the contract manufacturers designed new products for other competitors, and the brand owner attempted to obtain market knowledge of other competitors through the contract manufacturers.…”
Section: Auxiliary Productssupporting
confidence: 89%
“…This is consistent with the view that internal R&D resources increase the success of innovative products in the market (Roper et al, 2008). In addition, the knowledge regarding new product innovation is derived from in-house R&D (Ganotakis & Love, 2012). The brand owner also sought to create new and first-class product specification ideas to meet customer demands.…”
Section: Innovative Productssupporting
confidence: 62%
See 3 more Smart Citations